The Risk Factors and Hospital Mortality of Percutaneous Coronary Intervention Patients in Prepandemic and During Pandemic COVID-19: A Systematic Review - Hidtsa Aqila Noor Arasyi; Rizky Pratama; Muhammad Hendi Saputra (Cardiovascular and Cardiometabolic Journal (CCJ), 2024)
Highlights: 1. COVID-19 pandemic remains one of the interesting subject to discuss due to its large scale impact. 2. PCI is one of the popularly known method to screen COVID-19, however, depending on the prior screening, this may or may not be conducted. Thus, its frequency is reviewed in this study. - Backgroud: The COVID-19 pandemic is a global health issue that impact healthcare systems. COVID-19 infections affect the risk factors and mortality in patients undergoing PCI. The aim of this study is to determine the differences in risk factors and mortality rates of patients undergoing PCI before and during the COVID-19 pandemic. Method: We performed a systematic search on risk factors and hospital mortality of PCI patients in prepandemic and during pandemic COVID-19. Study reporting patient after year 2022 are excluded. The article published between 2019 - 2022. The literature selection was conducted following the PRISMA algorithm. Result: Eight journals were utilized, ensuring their relevance, compatibility, and adherence to the inclusion and exclusion criteria. In this study, it is explained that there has been a decrease in the number of patients undergoing PCI procedures during the COVID-19 pandemic. The increase of risk factor and there is no significant different hospital mortality of PCI patients before and during pandemic.